The Relationship of Creativity in Learning Content Development and Social Media Behavior on the Learning Professionalism of Elementary School Teachers in Gunungwungkal Pati - Yayuk Hariyasasti; Edris Zamroni; Yuni Ratnasari (Jurnal Pendidikan Terapan, 2026)
This research is crucial to determine the extent to which educators' adaptation of technology and digital literacy in cyberspace has transformed into effective role models and tools for improving the quality of education. The purpose of this study is to analyze the relationship between creativity in developing learning content and learning professionalism, and the relationship between social media behavior and learning professionalism. This study employed quantitative research with a correlational survey approach. Through this approach, researchers can objectively describe, measure, and analyze the relationships between variables based on empirical data from elementary school teachers in the Gunungwungkal area of Pati. The population in this study was all elementary school teachers in the Gunungwungkal area. The sample of 31 teachers was selected using simple random sampling. The study involved three main variables: creativity in developing learning content and social media behavior as independent variables, and teacher learning professionalism as dependent variable. Each variable was measured through indicators compiled into a questionnaire instrument using a Likert scale of 1–5. The analysis used SmartPLS to evaluate the structural equation model (SEM-PLS) through two stages: the Outer Model (testing the validity and reliability of the instrument) and the Inner Model (testing the influence between variables). The research results show that creative content development has a positive relationship with learning professionalism, and social media behavior is also related to learning professionalism. Teacher creativity and social media behavior have been empirically proven to have a very strong correlation with improving teacher professional competence.